PERAN MEDECINS SANS FRONTIERES (MSF) DALAM MENGATASI KRISIS KESEHATAN DI SUDAN (2023-2024) - Febiryani, Fesi; Saeri, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The emergence of conflict that occurred on April 15 2023 in Sudan caused many Sudanese people to become victims. The increasing violence coupled with the collapse of the health system in Sudan has resulted in many victims injured due to conflict as well as patients with complaints of other illnesses experiencing a health crisis to recover their condition. Medecins Sans Frontieres (MSF), which is an international non-governmental organization, is present in Sudan to help overcome the health crisis that is occurring in that country. This research analyzes the role of MSF in helping overcome the health crisis in Sudan amidst the current conflict situation. This research is qualitative research with secondary data collection methods through journals, news, official websites and MSF's official social media. In analyzing the role of MSF, this research uses the theory of the role of NGOs (Non Governmental Organization) put forward by David Lewis and Nazneen Kanji. The results of this research show that MSF as an international NGO has two roles in Sudan during the 2023-2024 conflict period, namely as implementer and partner. As an implementer, MSF plays a role in distributing goods and services to Sudanese citizens who are experiencing a health crisis. MSF's role as a partner is to collaborate, especially with the Sudanese Ministry of Health, to help overcome the current crisis conditions. Keywords: Medecins Sans Frontieres (MSF), NGO, Sudan, Health